2012
DOI: 10.1128/aac.05986-11
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the Anti-HIV-1 Activity of Acyclovir: Suppression of Primary and Drug-Resistant HIV Isolates and Potentiation of the Activity by Ribavirin

Abstract: ABSTRACTMultiple clinical trials have demonstrated that herpes simplex virus 2 (HSV-2) suppressive therapy using acyclovir (ACV) or valacyclovir in HIV-1/HSV-2-infected persons increased the patient's survival and decreased the HIV-1 load. It has been shown that the incorporation of ACV-monophosphate into the nascent DNA chain instead of dGMP results in the termination of viral DNA elongation and directly inhibits laboratory strains of HIV-1. We evaluated here the anti-HIV acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
1
16
0
1
Order By: Relevance
“…Indeed, the effect of ACV on HIV VL was initially attributed to the suppression of HSV-2 replication followed by the suppression of HSV-2-triggered inflammation [48, 49]. However, we and others [30, 50, 51] have found that ACV also has a direct effect on HIV-1 after the drug is phosphorylated by HHV. The direct inhibitory effect of ACV on HIV VL observed ex vivo was recently confirmed in vivo in a double-blind crossover clinical trial [52].…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the effect of ACV on HIV VL was initially attributed to the suppression of HSV-2 replication followed by the suppression of HSV-2-triggered inflammation [48, 49]. However, we and others [30, 50, 51] have found that ACV also has a direct effect on HIV-1 after the drug is phosphorylated by HHV. The direct inhibitory effect of ACV on HIV VL observed ex vivo was recently confirmed in vivo in a double-blind crossover clinical trial [52].…”
Section: Discussionmentioning
confidence: 98%
“…The assay developed by Biancotto et al (Biancotto et al, 2009) using mAb 4F6 as a C-Ab has demonstrated a great ability to measure concentrations of HIV-1 belonging to B subtypes (Balzarini et al, 2013; Introini et al, 2013; Merbah et al, 2012; Parrish et al, 2013; Saba et al, 2010; Vanpouille et al, 2012); however, its capacity to measure p24 from multiple non-B samples was more limited and opened the door for an assay using a more universal C-Ab. Biancotto et al .…”
Section: Discussionmentioning
confidence: 99%
“…As for all immunological assays, the success relies on the avidity and specificity of the C-Abs selected. Biancotto et al (Biancotto et al, 2009) developed a sensitive assay for the detection of p24 using the Luminex technology that has been used in many HIV-1 subtype B studies (Balzarini et al, 2013; Introini et al, 2013; Merbah et al, 2012; Parrish et al, 2013; Saba et al, 2010; Vanpouille et al, 2012). However, the C-Ab described by Biancotto et al lacks sensitivity for some HIV-1 non-B subtypes which account for almost 90% of HIV-1 infections worldwide (Hemelaar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…HIV-1 p24 gag concentrations were 49 ± 3 ng/ml and 53 ± 3 ng/ml for HIV-1 BaL and HIV-1 LAI.04 stock, respectively. For more viral preparations used in our experimental setting see References 3 and 4.…”
Section: Materials and Reagentsmentioning
confidence: 99%